2007
DOI: 10.1111/j.1365-2664.2007.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving insect pest management through population genetic data: a case study of the mosquito Ochlerotatus caspius (Pallas)

Abstract: Summary 1.Rationalizing the use of chemicals in pest control programmes is a fundamental goal that is aided by the knowledge of patterns of population connectivity and historical demography. 2. In this study, we used both mitochondrial and nuclear markers to investigate the genetic structure and diversity of the northern Italian populations of Ochlerotatus caspius , a mosquito of great public health and economic impact in Mediterranean countries. 3. A substantial genetic homogeneity was found among populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 60 publications
4
50
0
3
Order By: Relevance
“…Population genetic studies are done with the application of many genetic markers, among them mitochondrial DNA sequences, mostly those encoding mtCOI and mtCOII. These have been successfully applied for the population studies of other insect species (Grapputo et al 2005, Porretta et al 2007, Albernaz et al 2012.…”
Section: Resultsmentioning
confidence: 99%
“…Population genetic studies are done with the application of many genetic markers, among them mitochondrial DNA sequences, mostly those encoding mtCOI and mtCOII. These have been successfully applied for the population studies of other insect species (Grapputo et al 2005, Porretta et al 2007, Albernaz et al 2012.…”
Section: Resultsmentioning
confidence: 99%
“…This type of control is independently applied by breeders, in accordance with individual and shortterm necessity, without any coordinated program. The wide range of insecticides used to control pests can cause problems, such as environmental contamination (see Porretta et al 2007) and the selection of insecticide resistant strains (Cassida andGary 1998, Hemingway andRanson 2000). In the screwworm, Carvalho et al (2009) and Silva and Azeredo-Espin (2009) found mutations that are correlated with insecticide resistance.…”
mentioning
confidence: 99%
“…In the screwworm, Carvalho et al (2009) and Silva and Azeredo-Espin (2009) found mutations that are correlated with insecticide resistance. Thus, the necessity to reduce the use of chemicals and adopt control programs with enhanced speciÞcity for the target species, on the appropriate geographic scale, has been highlighted as a more suitable alternative (Kongan 1998, Porretta et al 2007.…”
mentioning
confidence: 99%
“…This region, known as the DNA barcode (Barcode of Life Initiative, 2003), was used previously to study the Iranian O. caspius (Azari-Hamidian et al, 2009). For O. caspius in Italy, microsatellite and allozyme polymorphism and mitochondrial COII gene structure are reported (Porretta et al, 2007). Although the nucleotide structure of the ITS2 area of C. pipiens is variable it cannot be used to distinguish between C. pipiens and C. pipiens f. molestus, however, a method based on the analysis of the 5'end of the mitochondrial COI gene can be successfully used to identify mosquitoes of the C. pipiens comlex (Shaikevich, 2007).…”
Section: Introductionmentioning
confidence: 99%